Understanding Morphology for Mass Communication: A Pragmatic Approach to English Language Teaching - Dey, Sadhan Kumar (International Journal of Mass Communication, 2023)
Mass Communication has become an essential phenomenon for global business transaction in recent times. Side by side, the English language has also become a global lingua franca for day -to-day use in all sorts of business transactions and socio-economic protocals of Mass Communication. The present paper is an humble effort to review the application of Morphology in English language and its implication in Mass Communication which inter alia requires focussed Vocabulary and Grammar in different global varieties of English language. The present article has also considered pidginized and creolized variety of English language in its application for Business communication that has become an integral part of global networking of Mass Communication through print media and Electronic media as well.